A comparative evaluation of pedestrian facilities outside schools: current conditions against design guidelines - Osman, Naimah; Nasrudin, Na’asah; Abdullah, Yusfida Ayu (UiTM Press, 2025)
This study assesses the condition of pedestrian facilities outside school areas by comparing the findings from site observations with established design guidelines derived from national and global practices. The research uses qualitative data from site observations conducted in five (5) primary schools in Shah Alam. School selection was based on similar socioeconomic characteristics, land use, and geographical proximity. The findings indicate that the existing pedestrian facilities significantly fail to meet the requirements outlined in current design guidelines. Critical deficiencies include inadequate infrastructure, poor maintenance, and the presence of obstacles that hinder safe pedestrian movement. Furthermore, the analysis reveals a lack of proactive oversight and maintenance by the responsible authorities, exacerbating safety risks for schoolchildren and community members who use the facilities. This paper highlights the urgent need for improved design, regular maintenance, and increased investment in pedestrian infrastructure to enhance safety and accessibility around schools. Recommendations are provided to local authorities to foster a safer walking environment for children and promote active transportation within the community.